Perilaku Ibu Balita Tentang Cuci Tangan Pakai Sabun Dan Kejadian Diare Pada Balita - Putri Lavena; Sri Lestari Adriyanti (Jurnal Sehat Mandiri, 2017)
The type of this research is descriptive that is to see the description of mother toddler's behavior about handwashing with soap and diarrhea occurrence at toddler in RW VI Kelurahan Limau Manis Selatan Kecamatan Pauh of Padang City. The population of this study is the mother who has a toddler who numbered 103 people and a sample of 51 people. This research was done by interview and observation and data analysis was done univariate analysis. The result of this research is found 54.9% the mother of toddlers has low knowledge, the mother of toddlers has negative attitude 52,9%, the mother of toddlers has bad action 60,8% and incidence of diarrhea in toddler is 58,8%. Health center should more often socialize the way and the importance of washing hands with soap regularly by using media poster and leaflet or counseling homes of the community. For the mother of toddler should follow counseling from health center and also dig information about handwashing with soap from social media and other print media.